Treasure island - Stevenson, Robert (OUP Oxford, 2005)
Jim Hawkins lives at an inn with his mother and father. One day an old sailor is killed there. In his bag, Jim finds a map of an island, with red crosses on it. Jim's friends, Squire Trelawney and Dr Livesey, say it is a treasure map. It shows where pirates have hidden their gold. Jim goes with his friends to find the gold. The squire finds a ship, but some of the sailors that he chooses are pirates. They want the treasure for themselves. They will kill anyone who tries to stop them. Jim finds out about their plans, but what can a boy do to stop Long John Silver and his evil pirates?